Scrolling, Clicking, Thinking: The New Psychology of the Digital Native - Romero, Cyril B.; Temena, Marc Jhames R. (Advances in Psychological Sciences and Applications, 2025)
This paper explores the evolving psychology of the Digital Native, a term commonly used to describe individuals who have grown up in the digital age and are inherently familiar with technology. With the advent of the internet and its ubiquity in everyday life, the behaviors, cognitive patterns, and mental frameworks of individuals have drastically shifted. The objective of this article is to present a critical examination of the psychological implications of this digital immersion and offer a conceptual framework for understanding the interaction between scrolling, clicking, and thinking in the context of the Digital Native. This paper employs a comprehensive literature review to analyze recent research on the digital behaviors and cognitive patterns of Digital Natives, using sources published within the last decade for up-to-date insights. Digital Natives' constant digital immersion reshapes cognition, leading to efficiency in information use but also to overload, distraction, and reduced critical thinking. This shift impacts education, work, and development, requiring strategies that support deep thinking and focus.